2016
DOI: 10.1007/s00415-015-7913-2
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization, prognosis and outcomes of vestibular disease in primary care settings: systematic review

Abstract: Vertigo and dizziness are frequent complaints in primary care that lead to extensive health care utilization. The objective of this systematic review was to examine health care of patients with vertigo and dizziness in primary care settings. Specifically, we wanted to characterize health care utilization, therapeutic and referral behaviour and to examine the outcomes associated with this. A search of the MEDLINE and EMBASE databases was carried out in May 2015 using the search terms ‘vertigo’ or ‘dizziness’ or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 48 publications
2
61
0
5
Order By: Relevance
“…Although some studies have reported a similar effect on symptom resolution in patients treated with the EM regardless of whether they had a positive DHT with or without nystagmus, 9,25 the authors found that the manoeuvre only resulted in significant improvements in DHT responses and vertigo severity in patients with nystagmus. In view of the conflicting results, the authors believe that the decision to treat patients with a positive DHT without nystagmus should be taken at the clinician's discretion, on a case-by-case basis.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…Although some studies have reported a similar effect on symptom resolution in patients treated with the EM regardless of whether they had a positive DHT with or without nystagmus, 9,25 the authors found that the manoeuvre only resulted in significant improvements in DHT responses and vertigo severity in patients with nystagmus. In view of the conflicting results, the authors believe that the decision to treat patients with a positive DHT without nystagmus should be taken at the clinician's discretion, on a case-by-case basis.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…8 Little is known about the use of the EM in primary care, even though approximately 60% to 80% of patients with BPPV are first seen by a GP. There have also been reports of suboptimal management of vertigo and BPPV in this setting due to poor awareness 9 and inadequate use of diagnostic and treatment tools. [10][11][12][13] Munoz et al 14 reported an improvement in nystagmus (evaluated by the DHT), but not in vertigo symptoms, 1 week after treatment in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reasons are restrictions in mobility, falls and secondary psychological consequences like anxiety, panic disorders or depression [4,5]. In chronic vestibular disorders, several factors were identified, which contribute to symptom severity, HRQoL and psychological comorbidity [6][7][8]. Symptom intensity in chronic central and functional vestibular disorders is higher than in peripheral vestibular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…identi cation of appropriate patients was di cult and cannot be explained by characteristics of the GP practices alone. We hypothesize the frequently reported problem of diagnosing VBD, which favours extensive health care utilization [14,15] might have led to that issue.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of these symptoms are common reasons for consultation in general practice, with stated consultation prevalence up to 15.5% [10]. Due to multifactorial aetiology [8,[11][12][13], the overutilization of health care in affected patients insu ciently treated in primary care has been shown [14,15]. Physical therapy is likely to be a valuable component in the management of patients with VDB regarding consequences like imbalance and falls that result in limited mobility and participation restrictions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%